Identification of the Hypervirulent Lineages of Neisseria meningitidis, the ST-8 and ST-11 Complexes, by Using Monoclonal Antibodies Specific to NmeDI - Claus, Heike (American Society for Microbiology, 2003)
Most cases of serogroup C meningococcal disease are caused by the clonal lineages ST-8 and ST-11. The gene encoding the putative restriction-modification system NmeDI is specific to these lineages. We report here a monoclonal antibody directed against the NmeDI endonuclease as a tool for their rapid and spe-cific identification.